2016
DOI: 10.4142/jvs.2016.17.4.587
|View full text |Cite
|
Sign up to set email alerts
|

First detection ofWest Nile virusin domestic pigeon in Korea

Abstract: West Nile virus (WNV) is a mosquito-borne zoonotic pathogen that has spread throughout Europe and the United States. Recently, WNV spread to East and Southeast Asia, and great efforts have been made in South Korea to prevent the spread of WNV from neighboring countries. In this study, we diagnosed the first case of WNV in pigeons (Columba livia domestica) residing in cities using a competitive enzyme-linked immunosorbent assay and confirmed it with nested reverse transcription polymerase chain reaction analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…A study conducted in the city of Bauchi (in the North East zone of Nigeria) reported an approximately 3.5% prevalence of WNV IgG in pigeons. A comparable report reported levels of WNV IgG in pigeons that migrate to urban centers in search of food and nesting areas [ 44 ]. These pigeons come into direct proximity with humans, enhancing the zoonotic transmission of WNV from the birds to humans.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the city of Bauchi (in the North East zone of Nigeria) reported an approximately 3.5% prevalence of WNV IgG in pigeons. A comparable report reported levels of WNV IgG in pigeons that migrate to urban centers in search of food and nesting areas [ 44 ]. These pigeons come into direct proximity with humans, enhancing the zoonotic transmission of WNV from the birds to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Human cases of WNV infection were also reported in western China in 2011, and WNV was simultaneously isolated from mosquitoes in the affected area (195). The WNV gene was detected from domestic pigeons in Korea in 2014 (196). It was recently demonstrated that sporadic cases of severe lymphoplasmacytic meningoencephalitis were associated with WNV in California (197).…”
Section: Mosquito-borne Arbovirusesmentioning
confidence: 99%
“…7, 8 Although WNV is an emerging pathogen in China and East Asia, 9 there have been no recent reports of WNV encephalitis cases or epidemics in the region. Determining the incidence of WNV infection has become an important public health concern.…”
mentioning
confidence: 99%
“…WNV was first isolated in mainland China from mosquito specimens in Jiashi County, Kashi Region, southern Xinjiang, following local outbreaks of viral meningitis and encephalitis caused by WNV. 7 , 8 Although WNV is an emerging pathogen in China and East Asia, 9 there have been no recent reports of WNV encephalitis cases or epidemics in the region. Determining the incidence of WNV infection has become an important public health concern.…”
mentioning
confidence: 99%